2021
DOI: 10.1136/bmjopen-2021-049010
|View full text |Cite
|
Sign up to set email alerts
|

Are sexual health survey items understood as intended by African and Asian migrants to Australia? Methods, results and recommendations for qualitative pretesting

Abstract: IntroductionMore research and policy action are needed to improve migrant health in areas such as sexual health and blood-borne viruses (SHBBV). While Knowledge, Attitudes and Practice Surveys (KAPS) can inform planning, there are no SHBBV KAPS suitable for use across culturally and linguistically diverse contexts. This study pretests one instrument among people born in Sub-Saharan Africa, South-East and North-East Asia living in Australia.MethodsEmployees of multicultural organisations were trained to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For example, Ahlmark et al reported that content and language of questionnaires are barriers for immigrant and non‐Western descendants in responding to surveys 38 . Even if patients are familiar with English, but are not fluent, survey items may not be completely understood as intended due to cultural or religious contexts 39 . Since non‐English speaking patients are less likely to complete Sexual Well‐being, strategies to improve survey collection in these populations are necessary 40 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ahlmark et al reported that content and language of questionnaires are barriers for immigrant and non‐Western descendants in responding to surveys 38 . Even if patients are familiar with English, but are not fluent, survey items may not be completely understood as intended due to cultural or religious contexts 39 . Since non‐English speaking patients are less likely to complete Sexual Well‐being, strategies to improve survey collection in these populations are necessary 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We also included in our models all variables related to participants' characteristics that were significantly associated with each outcome in bivariate regressions (p ≥ 0.10), except for sex and oral French proficiency, which were systematically maintained in the analysis even if the p values in the bivariate analysis were not significant. These variables were maintained in the analysis to control for potential sex differences and the fact that the language proficiency can influence the participants' understanding of the survey items ( Vujcich et al, 2021 ). Variables checked included participants’ characteristics listed in the descriptive analysis (Section 2.2.2 ) and the following: children; mental health status using the Patient Health Questionnaire (PHQ-9) developed by Kroenke et al (2001) ; social workers who delivered the intervention; and ability to express needs to a social or health professional during referral.…”
Section: Methodsmentioning
confidence: 99%
“…Such measurement error and caveated conclusions are partly because measures arising from validated instrument are not fixed but dependent on context and population [ 69 , 71 ]. Notably, Australian-based migrants, who come from African and Asian backgrounds, may have difficulties understanding sexual health survey items as intended [ 72 ]. Thus, the decision to develop my own measure was informed by a need to use measures that are contextualised to the target groups in this study.…”
Section: Methodsmentioning
confidence: 99%
“…This pretesting was partly done to ensure the items of the questionnaire were clear from the perspective of potential participants. Ensuring clarity of the questionnaire items is important because Australian-based migrants, who come from African and Asian backgrounds, may have difficulties understanding sexual health survey items as intended [ 72 ]. Feedback from the pilot was used to shorten the length and further improve the wordings of the questionnaire for greater clarity.…”
Section: Methodsmentioning
confidence: 99%